False-positive galactomannan assay in broncho-alveolar lavage after enteral nutrition solution inhalation: a case report. (18th September 2017) - Lheureux, Olivier; Montesinos, Isabel; Taton, Olivier; Antoine, Martine; Preiser, Jean-Charles; Nortier, Joelle; Creteur, Jacques; Jacobs, Frederique; Grimaldi, David
Abstract : Introduction. Diagnosis of invasive aspergillosis is challenging and the gold standard for definite diagnosis remains histopathological tissue examination. However, invasive procedures such as lung biopsy are often not feasible in critically ill patients. The detection of fungal cell wall components like Aspergillus galactomannan in broncho-alveolar lavage remains a key component of the diagnostic procedure. False-positive of the Aspergillus galactomannan assay is not frequent. Case presentation. We report a case of positive galactomannan in broncho-alveolar lavage fluid after enteral nutrition aspiration without signs of invasive aspergillosis. Galactomannan was positive in the enteral nutrition solution. Conclusion. Physicians should be aware of this previously unrecognized cause of false-positive galactomannan in broncho-alveolar fluid which can result in unnecessary treatments.